The Effect Of Talent Management And Transformational Leadership On Organizational Performance With Work Engagement And Perceived Organizational Support As Mediation At MAN 1 Jepara - Rahmat Arif Syaifudin; Sisno Riyoko; Hadi Ismanto (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study was conducted to analyze the influence of talent management and transformational leadership on organizational performance with work engagement and perceived organizational support as mediators at MAN 1 Jepara. Using a quantitative approach by conducting a survey of 92 respondents consisting of educators and education personnel through a questionnaire with a Likert scale of 1-10. Data were analyzed using SmartPLS software to determine the significance and strength of the relationship between variables. The results showed that organizational performance was significantly influenced by perceived organizational support and work engagement. Transformational leadership and talent management did not have a direct effect on performance, but both had an indirect effect through employee psychological mechanisms. Transformational leadership improved performance through perceived organizational support, while talent management through work engagement. These findings confirm that the improvement in madrasah organizational performance occurs through strengthening work engagement and perceived organizational support by employees. Keywords: Talent Management, Transformational Leadership, Organizational Support, Work Engagement, Perceived Organizational Support